United States Trade and Investment Missions to Africa, Jan. 8 - 21 '82 (Washington D.C.: U.S. Department of Commerce, U.S. Department of Agriculture, 1981)
The book provides a profile of individuals and firms that were on trade and investment missions to Africa, in Jan. 8 - 21 '82
osc 17/05/2019
Arch
Keywords: Trade; Investment; Africa; Nigeria